The structural and relational capital in the organizational performance of the public sector in the state of Tamaulipas (Mexico): An exploratory factor and correlational analysis using Spearman’s Rho - Flores Flores, Adán Jacinto; Lavín Verástegui, Jesús; Castillo Hernández, Lázaro (Acta Universitaria, 2021)
The objective of this work is to empirically determine the association of structural capital (SC) and relational capital (RC) with organizational performance (OP) in the public sector of the state of Tamaulipas (Mexico). From October to December 2019, 269 surveys were applied in person and online. The data collected were interpreted using an exploratory factor analysis (EFA) and the Spearman’s Rho correlation coefficient. A two-factor structure was established for SC (1. Organizational innovation and 2. Organizational structure), a three-factor structure for RC (1. Long-term relationships with users, 2. Long-term relationships with suppliers, and 3. Strategic alliances), and a three-factor structure for OP (1. Civic behavior, 2. Companionship, and 3. Initiative). The factors Long-term relationships with users and Strategic alliances have the highest level of statistical association with OP.